The Character of Early Childhood Education: Perspectives of Ki Hajar Dewantara and Maria Montessori - Andrianto, Dedi; Kurniawan, Wakib (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This research explores the concept of character education for pre-school children based on the perspectives of Ki Hajar Dewantara and Maria Montessori. This research uses a qualitative approach with a comparative analysis method to highlight the similarities and differences of these two educational pioneers. Ki Hajar Dewantara emphasised the integration of local wisdom, independence, and moral values through the principles of ‘Ing Ngarsa Sung Tuladha’ (setting an example), ‘Ing Madya Mangun Karsa’ (building motivation), and ‘Tut Wuri Handayani’ (supporting from behind). In contrast, Maria Montessori focused on developing independence, discipline, and a sense of responsibility through structured learning environments, individualised learning plans, and the use of didactic materials. Despite their different cultural and historical contexts, both approaches share the common goal of fostering children's character as a foundation for lifelong development. The study concludes by emphasising the relevance of these two perspectives in designing a holistic character education model that addresses cognitive, emotional, and social dimensions for early childhood education.